2013
DOI: 10.1371/journal.pone.0079218
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Microtiter Plate Based Method for the Determination of Peracetic Acid and Hydrogen Peroxide

Abstract: Peracetic acid is gaining usage in numerous industries who have found a myriad of uses for its antimicrobial activity. However, rapid high throughput quantitation methods for peracetic acid and hydrogen peroxide are lacking. Herein, we describe the development of a high-throughput microtiter plate based assay based upon the well known and trusted titration chemical reactions. The adaptation of these titration chemistries to rapid plate based absorbance methods for the sequential determination of hydrogen perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…tive detection of H 2 O 2 (29). Unfortunately, control experiments conducted during this study indicate that H 2 O 2 is unstable under these reaction conditions and, therefore, cannot be accurately detected by this method (Fig.…”
Section: O 2 -Dependent Lthdp Decarboxylation On Dxp Synthasementioning
confidence: 85%
See 1 more Smart Citation
“…tive detection of H 2 O 2 (29). Unfortunately, control experiments conducted during this study indicate that H 2 O 2 is unstable under these reaction conditions and, therefore, cannot be accurately detected by this method (Fig.…”
Section: O 2 -Dependent Lthdp Decarboxylation On Dxp Synthasementioning
confidence: 85%
“…To distinguish between paths A and B/C ( Fig. 4), we utilized two previously described biochemical assays that specifically monitor peracetic acid (path A) or H 2 O 2 (paths B or C) formation (20,29). DXP synthase-catalyzed peracetic acid formation was probed using a coupled assay with thionitrobenzoate (TNB, max ϭ 412 nm), which is readily oxidized by peracetic acid at a significantly higher rate (ϳ3000-fold higher) compared with its oxidation by H 2 O 2 (20), thus providing a selective detection method to differentiate between peracetic acid and H 2 O 2 production.…”
Section: O 2 -Dependent Lthdp Decarboxylation On Dxp Synthasementioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is an important analyte, and its determination plays a key role in different fields, such as biology, biomedicine, the food industry, and pharmaceutical, biochemical, and environmental analyses. , Moreover, it is involved in several biological processes, and its excess can affect the proper functioning of cells; thus, its accurate determination is valuable . Over the years, different techniques have been explored for its determination, such as titrimetry, chromatography, spectrophotometry, colorimetry, fluorescence, and electrochemistry . However, electrochemical methods are preferred due to their rapid development, good accuracy, lower detection limits, easy miniaturization, biocompatibility, low cost, simple instrumentation, high selectivity, and fast response. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported adsorption of known chemical and gas sterilants (hydrogen peroxide and EtO) onto polymers with some polymer absorbing considerable amounts of H 2 O 2 in less than an hour. [32,35] Studies exist in the literature regarding use of STS and catalase to remove residual concentrations of PA. [36]. Radl et al demonstrated that desorption kinetics from polymers exposed to hydrogen peroxide showed a strong dependence on the material composition and temperature [29].…”
Section: Discussionmentioning
confidence: 99%